Peripartum type A dissection: a case report - Sanrı, Umut Serhat; Özsin, Kadir Kaan; Toktaş, Faruk; Yavuz, Şenol (The European Research Journal, 2018)
Aortic dissection is a rare but potentially lethal complication during pregnancy in young women and usually diagnosis could be overlooked. We reported a 40-year-old postpartum female with aortic dissection which developed in peripartum period. She complained of interscapular back pain and chest pain. The patient's  pain had continued after caesarean section. She admitted to our clinic six days after this intervention. Contrast-enhanced computed tomography revealed the aortic dissection. Hemiarch replacement performed successfully and the patient discharged uneventfully despite of delayed diagnosis.